2018
DOI: 10.3390/ijerph15081636
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polybrominated Diphenyl Ethers on Child Cognitive, Behavioral, and Motor Development

Abstract: Polybrominated Diphenyl Ether (PBDE) flame retardants are environmental chemicals that cross the placenta during pregnancy and have shown evidence of neurotoxicity. As the in utero period is a sensitive developmental window, such exposure may result in adverse childhood outcomes. Associations between in utero PBDE exposure and neurodevelopment are found in animal models and increasingly in human population studies. Here, we review the epidemiological evidence of the association between prenatal exposure to PBD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 42 publications
(127 reference statements)
1
25
0
2
Order By: Relevance
“…It is still unclear if PBDE exposure may affect child motor control. Most studies have not detected significant associations, 16 18 , 24 , 41 and similarly, our study is in line with that research. However, two studies suggested a negative association between motor development and PBDE exposure.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is still unclear if PBDE exposure may affect child motor control. Most studies have not detected significant associations, 16 18 , 24 , 41 and similarly, our study is in line with that research. However, two studies suggested a negative association between motor development and PBDE exposure.…”
Section: Discussionsupporting
confidence: 93%
“…The association between child attention and PBDE exposure has been well investigated. 16 Previous animal studies suggested that PBDE exposure can affect sustained attention and can increase hyperactivity. 42 , 43 Similarly, studies in children have detected correlations between PBDE exposure and child attention deficits.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent reviews and a meta-analysis, neurodevelopmental impacts, and IQ in particular, are among the most consistently observed outcomes, and additional evidence suggests thyroid disruption as one of several potentially contributing biological pathways (Costa et al. 2014; Gibson et al. 2018; Lam et al.…”
Section: Methodsmentioning
confidence: 99%
“…They are used as flame retardants, also in wire insulation and cars [ 119 ]. They get into the human body through the respiratory and digestive tract, and they also cross the blood-placenta barrier ( Figure 5 ) [ 120 , 121 , 122 , 123 ].…”
Section: Flame Retardants (Frs)mentioning
confidence: 99%